Juridical Analysis of the Legal Standing of Insurance Companies Creditors in Bankruptcy and Suspension of Debt Payment Obligations Application - ., Dedy; Siregar, Mahmul; Sukarja, Detania; ., Haswandi (KnE Social Sciences, 2024)
This article aims to discuss and analyze the legal position of insurance company debtors in bankruptcy and PKPU proceedings. It also seeks to explore further the rationale and objectives of conferring the authority to file bankruptcy or PKPU proceedings for insurance companies on OJK. The research applies normative juridical research method. The article concludes that since the issuance of Law Number 21 of 2011 concerning the Financial Services Authority was issued, the authority over insurance companies, including the legal standing for bankruptcy application, was transferred to OJK. Such stipulation is reaffirmed in Law Number 40 of 2014 concerning insurance. The authority of OJK on bankruptcy applications for insurance companies is justified to protect the public interest. Even though the applicable legal provisions do not explicitly state that the specific requirement for bankruptcy applications against insurance companies also apply to PKPU proceedings, it should also apply mutatis to PKPU proceedings. Both proceedings against insurance companies might have an impact on the economy. In both bankruptcy and PKPU proceedings, equal treatment should not be given to creditors because the interests of the state are greater than those of the creditors. Therefore, the authority of the OJK to file for bankruptcy of insurance companies must be interpreted as the authority to file for PKPU for insurance companies. Keywords: bankruptcy, suspension of debt payment obligations, insurance